Factura - Harvey, Steven (New York : Gallery Schlesinger-Boisanté, Inc., 1985)
Barth, Jack ; Belag, Andrea ; Bleckner, Ross ; Botts, Gregory ; Deutsch, David ; Fowler, Roy ; Krall, L. Brandon ; Morrison, Richard ; Nares, James ; Nelson, David ; Rice, Bill ; Van Vliet, Don ; White, Shawn ; Wool, Christopher
Factura, Gallery Schlesinger-Boisanté, Inc., New York, May 14 - June 15, 1985
boek